Transferência de humidade em paredes de edificios - Analise do fenómeno de interface - Vasco Freitas (1992)
The study of the moirtura migration in the inner parts of materials and construction components is of great importance for its behaviour's characterization. Namely, in what concerns its durability, its waterproofing, its degrading appearance and its thermal performance. In the present study the different mechanisms of moisture transport in the building walls were studied. Bsed on the theory proposed by Luikov-Philip and De Vries, a program of automatic calculus was developed, allowing us to foresee, by simulation, the temporal variation of the water content and of the temparature profiles in the inner parts of the building components according to the inner and outer climate conditions. A data base with physical and hygrothermal characteristics of some of the construction materials was created, which is indispensable to the numerical simulation of the transfer phenomenon. Using a moisture measurement device based on the principle of attenuation of gamma-ray, installed at the hygrothermal laboratory of the FEUP - Engineering Faculty of OPorto's University - we are able to test the development of the water content profiles of the buildings walls and the moisture migration in the interface between layers for several contact shapes. The comparison between the numerical and experimental results allowed us to validate quality wise the computer model - TRHUMIDADE. The numerical simulations and tests made, gave important information about: the influence of the solar radiation on the walls drying; the influence of moisture in the decreasing of the thermal resistance; the influence of the rain and condensation on the walls moisture and the influence of the interface on the wetting and drying of kinetics of multiple layer walls. Key words: Moisture, moisture migration, walls, buildings, moisture measurement, gamma-ray, computer model